2023
DOI: 10.1007/s11046-023-00720-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Changing Dermatophyte Spectrum in India Through Analysis of Cumulative 161,245 Cases Between 1939 and 2021

Abstract: Dermatophytosis is one of the most common superficial infections of the skin affecting nearly one-fifth of the world population at any given time. With nearly 30% of worldwide terbinafine-resistance cases in Trichophyton mentagrophytes/Trichophyton interdigitale and Trichophyton rubrum reported from India in recent years, there is a significant burden of the emerging drug resistance epidemic on India. Here, we carry out a comprehensive retrospective analysis of dermatophytosis in India using 1038 research arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…13 For instance, one study found that certain haplotypes were more frequently associated with severe cases of tinea capitis, while others were more frequently associated with less severe cases. 30 Overall, haplotype analysis of T. tonsurans has provided valuable insights into its genetic diversity, population structure and evolution, as well as its interactions with human hosts and the development of antifungal drug resistance. 30 In our study, 24 haplotypes were found, eight of which were dominant and two of which were more common than the others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 For instance, one study found that certain haplotypes were more frequently associated with severe cases of tinea capitis, while others were more frequently associated with less severe cases. 30 Overall, haplotype analysis of T. tonsurans has provided valuable insights into its genetic diversity, population structure and evolution, as well as its interactions with human hosts and the development of antifungal drug resistance. 30 In our study, 24 haplotypes were found, eight of which were dominant and two of which were more common than the others.…”
Section: Discussionmentioning
confidence: 99%
“…30 Overall, haplotype analysis of T. tonsurans has provided valuable insights into its genetic diversity, population structure and evolution, as well as its interactions with human hosts and the development of antifungal drug resistance. 30 In our study, 24 haplotypes were found, eight of which were dominant and two of which were more common than the others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rubrum is among the most frequently detected species globally and is responsible for 50%-90% of dermatophytoses (9)(10)(11)(12)(13). However, a sudden shift in the most prevalent pathogen from T. rubrum to T. mentagrophytes complex in India has been observed in recent years, which might result from advances in molecular identification (14). Other important species include Microsporum canis, Epidermophyton floccosum, and T. tonsurans (Table 1) (22,30,31).…”
mentioning
confidence: 99%